2015
DOI: 10.2147/dddt.s73551
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-microRNA-181a is a regulator of a number of cancer genes and a biomarker for endometrial carcinoma in patients: a bioinformatic and clinical study and the therapeutic implication

Abstract: The aberrant expression of human microRNA-181a-1 (hsa-miR-181a) has been implicated in the pathogenesis of various cancers, serving as an oncogene or a tumor suppressor. However, the role of hsa-miR-181a in the pathogenesis of endometrial carcinoma (EC) and its clinical significance are unclear. This study aimed to search for the molecular targets of hsa-miR-181a using bioinformatic tools and then determine the expression levels of hsa-miR-181a in normal, hyperplasia, and EC samples from humans. To predict the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 119 publications
(200 reference statements)
0
19
0
Order By: Relevance
“…A recent study suggested oncogenic role for hsa-miR-181a in endometrial tumorigenesis and its critical role in tumor metastasis of advanced EC (He et al 2015).…”
Section: Role Of Epigenetic Modifications and Mirna Regulationmentioning
confidence: 99%
“…A recent study suggested oncogenic role for hsa-miR-181a in endometrial tumorigenesis and its critical role in tumor metastasis of advanced EC (He et al 2015).…”
Section: Role Of Epigenetic Modifications and Mirna Regulationmentioning
confidence: 99%
“…To understand the molecular mechanisms underlying miR-101-3p effect on the trans-endothelial migration ability of BC cells, we searched for its potential pro-metastasis target genes using six prediction databases including mirTarBase 7.0, miRanda-mirSVR (microRNA.org), PicTar, miRDB, TargetScan 7.2 and TarBase v7.0 [ 31 , 32 ]. In our search, we focused on the genes involved in transmigration of BC through the brain endothelium, particularly, HBEGF, PTGS2 and ST6GALNAC5.…”
Section: Resultsmentioning
confidence: 99%
“…In silico bioinformatics analysis was carried out to identify miR-101 target genes that are involved in transmigration of cancer cells through the brain endothelium. Initially, we searched for the targets of miR-101-3p using 6 prediction databases including mirTarBase 7.0, miRanda-mirSVR (microRNA.org), PicTar, miRDB, TargetScan 7.2 and TarBase v7.0 [ 31 ]. The target genes identified in more than 3 databases were retained.…”
Section: Methodsmentioning
confidence: 99%
“…In silico bioinformatics analysis was carried out to identify micro-RNAs that directly target the 3'-UTR of MMP1. We searched for the micro-RNAs using four databases: mirTarBase 7.0, miRanda-mirSVR (microRNA.org), and miRDB, TargetScan 7.2 [42].…”
Section: In Silico Bioinformatics Analysismentioning
confidence: 99%
“…To identify the micro-RNAs that are specifically involved in the upregulation of MMP-1 in brain metastatic breast cancer cells, we analyzed the clinical micro-RNA array cohort data (GSE37407) which contains global microRNA profiling performed on primary breast tumor samples from 10 patients and their corresponding paired brain metastatic tumors [36]. Analysis with the GEO2R tool of the top 250 microRNAs differentially expressed between the primary and brain metastatic breast tumors revealed that five microRNAs are downregulated in brain metastatic tumors compared to breast primary tumors and also predicted to target MMP1 using four prediction databases: mirTarBase 7.0, miRanda-mirSVR (microRNA.org), and miRDB, TargetScan 7.2 [42]: miR-202-3p, miR-326, miR-623, let-7c, and miR-145 (S1 Table). Three of these micro-RNAs (miR-202-3p, miR-623 and miR-145) are validated to target MMP1 [26,32,45].…”
Section: Mir-202-3p Expression Is Attenuated In Brain Metastatic Breamentioning
confidence: 99%